2020
DOI: 10.11604/pamj.supp.2020.35.2.23644
|View full text |Cite
|
Sign up to set email alerts
|

Novel coronavirus disease 2019: knowledge, practice and preparedness: a survey of healthcare workers in the Offinso-North District, Ghana

Abstract: Introduction Ever since World Health Organization declared COVID-19 as a public health emergency of international concern, Ghana is one of the most affected countries in Africa. However, the knowledge, practice, and preparedness of healthcare providers on the novel COVID-19 in the country has not been studied. This study assessed health workers’ knowledge, practice, and preparedness on the current pandemic in three Ghanaian hospitals. Methods This multi-centre cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 19 publications
9
30
1
Order By: Relevance
“…More education is required in this direction to upscale the levels of knowledge associated with the observation above. Observation of the adequate knowledge about the common symptoms of SARS-COV-2 among the allied radiation medicine professionals in this study are similar to observations reported in studies such as Kotian et al [1] and Nkansah et al [4], in which knowledge of health professionals on COVID-19 were assessed.…”
Section: Level Of Knowledge On the Symptoms Of Covid-19supporting
confidence: 89%
See 1 more Smart Citation
“…More education is required in this direction to upscale the levels of knowledge associated with the observation above. Observation of the adequate knowledge about the common symptoms of SARS-COV-2 among the allied radiation medicine professionals in this study are similar to observations reported in studies such as Kotian et al [1] and Nkansah et al [4], in which knowledge of health professionals on COVID-19 were assessed.…”
Section: Level Of Knowledge On the Symptoms Of Covid-19supporting
confidence: 89%
“…In December 2019, the seventh coronavirus known to infect humans was found in China (Wuhan city, Hubei Province) [3] and on 12 January 2020, the World Health Organization (WHO) announced the temporarily named nCoV-2019, now called SARS-CoV-2. The WHO declared the disease a global pandemic in March 2020 [4,5]. Worldwide, 25.7 million people have been infected with COVID-19 since it was first identified, with about 850,000 deaths as at September 1, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…This might have led to a situation where hospital ancillary staff had not used PPEs or had used it improperly due to lack of knowledge or training on proper infection control measures including use of PPEs and other protection measures while handling patients and that this resulted in unprotected exposure amongst this group of HCWs in large numbers. The other plausible explanation for the higher rate of COVID-19 infection in hospital ancillary staff is that most patients remained undiagnosed during admission to hospital settings and it could be that owing to shortage of doctors and nurses in countries like Somalia, this A number of studies in Africa have also suggested that knowledge among frontline health workers on transmission risks remains low, necessitating educational training programmes to ensure adherence to standard precautionary measures (Nkansah et al, 2020) (Elhadi et al, 2020). However, many of these studies did not show a difference between different categories of HCWs, if any, in risk perception, knowledge or adherence to strict infection control/precautionary measures.…”
Section: Protecting Hcws: a Priority In View Of Shortagesmentioning
confidence: 99%
“…A number of studies in Africa have also suggested that knowledge among frontline health workers on transmission risks remains low, necessitating educational training programmes to ensure adherence to standard precautionary measures ( Nkansah et al, 2020 ) ( Elhadi et al, 2020 ). However, many of these studies did not show a difference between different categories of HCWs, if any, in risk perception, knowledge or adherence to strict infection control/precautionary measures.…”
Section: Protecting Hcws: a Priority In View Of Shortagesmentioning
confidence: 99%
“…18 Even though Nkansah et al, (2020) recently concluded that two-thirds (65.1%) of HCWs possess adequate knowledge on the COVID-19 pandemic, their study was limited to only one district in Ghana and had a smaller sample size as well. 19 This study was therefore destined to assess HCWs knowledge, perception and practice with regard to the current COVID-19 pandemic in the entire country.…”
mentioning
confidence: 99%